The Effect of Hotel Tax and Restaurant Tax on Local Own-Source Revenue (PAD) - Elfanda Bary Titania; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2022)
Regional Original Revenue (PAD) is regional revenue obtained from regional taxes, regional levies, the results of separated regional wealth management and other legitimate regional original revenues. Local taxes as the largest source of Regional Original Income (PAD), one of which comes from hotel taxes and restaurant taxes. The aims of this study are 1) to determine the effect of hotel tax on local revenue (PAD), 2) to determine the effect of restaurant tax on local revenue (PAD). The research method used is a quantitative method. The sample of this study uses secondary data obtained from the Regional Financial and Asset Management Agency (BPKAD), namely in the form of reports on the realization of hotel taxes, restaurant taxes and Regional Original Income (PAD) for 2019-2020. The analysis technique uses multiple linear regression, t test and coefficient of determination after all the data have met the requirements of the classical assumption test using SPSS version 25.0. Based on the research results, it is known that the hotel tax has a coefficient value of -79.039 and Sig 0.004 <0.05, meaning that hotel tax has a negative and significant effect on Regional Original Income (PAD). The restaurant tax has a coefficient value of 21.006 and Sig 0.007 <0.05, meaning that the restaurant tax has a positive and significant effect on Regional Original Income (PAD).